A double-layer dura mater based on poly(caprolactone-co-lactide) film and polyurethane sponge: preparation, characterization, and biodegradation study. Issue 18 (30th April 2021) - Jin, Shu; Pu, Yuji; Guo, Zhaoyuan; Zhu, Wangwei; Li, Sai; Zhou, Xi; Gao, Wenxia; He, Bin
Abstract : A double-layer composite of the PCLA film and PU sponge with good biodegradability and biocompatibility was designed as a potential dural substitute. Abstract : Synthetic, biodegradable polymers hold great potential in dura mater substitution. In this study, a dura mater-mimetic double-layer film@sponge composite was developed. The composite contains a poly(caprolactone- co -lactide) (PCLA) film and polyurethane (PU) sponge, which simulates the hard and soft layers of dura mater, respectively. PCLA films were prepared by a solution-casting method and showed excellent mechanical properties and tolerance to water. PU sponge was hydrophilic and had a high water-absorption rate (about 500%). The double-layer composite (film@sponge) integrated the good mechanical properties of the films and the good water absorption of the sponge. The excellent biocompatibility and biodegradability of the PCLA film@PU sponge composites were verified by in vitro degradation and cytotoxicity study and the in vivo implantation in the back of rats. Importantly, the film@sponge composite had a suitable degradation rate and good biocompatibility, holding potential in the field of dural repair.